(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Management of human resources in the tourism sector of Uzbekistan is gaining importance nowadays. The main purpose of psychological training is to develop professional and personal qualities of employees, to improve their attitude towards the organization and to strengthen mutual relations in the work team.